Menganalisis Peran Guru Mengenai Kesiapan Kegiatan Pembelajaran Dalam Mengahadapi Masa New Normal di Sekolah Dasar - Sri Wahyuni Saefudin; Luthfi Hamdani Maula (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Education creates a person of high quality and character so that he has a broad view in the future to achieve the ideals that are expected and able to adapt quickly and precisely in various environments. Unforeseen circumstances in the form of the Covid-19 disease outbreak have brought urgent changes in various sectors including the education sector. The new policy was made in the world of education, namely the technical changes face to face learning to be online. Recently a new policy has emerged called New Normal is to re-enact activities or activities of the general public, but still implemented with health protocols. This study has the aim to describe the role of teachers in the readiness of learning activities in elementary schools with the application of New Normal. The research method used is descriptive qualitative research method. Based on the results of the study found that teachers are ready to carry out learning in the new normal period by applying health protocols and making new regulations at school. So that from all of this research it can be concluded that the teachers at SDN 1 Cikembar already understand what will be done in learning in the new normal times that will be applied